Práticas de cuidados em tecnologia assistiva: o ponto de vista das mães - Macedo, Bárbara Caroline (2023)
Assistive Technology (AT) has been consolidated as an area of knowledge promoting the active participation of people with disabilities and their families in the definition of aspects that impact on their accessibility, as well as in the experimentation of technological alternatives and in the search for solutions. However, there is still a gap in the field of scientific research regarding the involvement of families of children with disabilities in the preparation of the AT plan and the inclusion of their knowledge in this plan. Therefore, this study aimed to question practices in AT from the perspective of mothers of children with disabilities combined with the theories of Ethics of Care and Psychoanalysis. To this end, the study included the autobiographical production of three mothers of children with disabilities about their experiences with AT services and resources. This is a qualitative, document-type study using care as an analytical category, and based on the following four pillars: dependency, otherness, relational autonomy and care network. The study focuses on the following aspects aiming at the progress of the scientific field of AT: 1) In opposition to the idea that understands the resource of AT with the purpose of overcoming the disability or restoring the body to a supposed natural condition, the resource can be seen as one of several possible supports in view of the character of dependency inherent to the human being, which will facilitate the activities of its users; 2) Unlike the implementation of a resource based on a generic decision based on empowering and universal conceptions of what it is to be a child, and given the principle of otherness in the field of assistive technology, tailored solutions are needed based on each case and each context , supported by the diversity of forms of existence and bodies; 3) According to the concept of relational autonomy, the implementation of assistive technology resources would be defined from a joint decision established in a care relationship, not being a prescriptive measure that is apart from the subject's particularities, but making the resource an important instrument to expand the children's activities and to act in favor of the social bond; 4) A care network is necessary to ensure that the child will have access and participation in the world, since actions based on elimination, segregation, exclusion and oppression are not the sole responsibility of a mother, nor are they private and dual relationships, but collective, as a duty of all and of the State